STEM Teachers' Motivation and Engagement in Teacher Professional Development and Career Advancement: A Case Study of Lithuania - Anita Juškevičienė; Tatjana Jevsikova; Gabrielė Stupurienė; Lina Vinikienė (MDPI AG, 2024)
The demand for science, technology, engineering, and mathematics (STEM) skills has been consistently increasing due to technological advancements and globalization, making STEM education and teacher training a critical priority. Although many national and international initiatives have been implemented to strengthen STEM education and raise the attractiveness of the teaching profession, a shortage of teachers in general, and STEM teachers in particular, is still evident across Europe. This study aimed to identify factors contributing to attracting existing and potential teachers to careers in STEM education. Qualitative research methods were employed to study teachers' perceived motivation, challenges, and suggestions regarding STEM teachers' careers, competence, and collaboration development. The study revealed that the practical application of competence development initiatives significantly motivates STEM teachers, emphasizing the importance of aligning professional development with classroom implementation. These results emphasize the importance of prioritizing practical, classroom-oriented professional development and fostering a culture of collaboration in educational institutions.